2010
DOI: 10.3109/10253890.2010.522630
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal diurnal pattern of cortisol secretion in patients after aneurysmal subarachnoid hemorrhage

Abstract: Substantial evidence suggests that impairment of the hypothalamus?pituitary system can occur following an aneurysmal subarachnoid hemorrhage (aSAH). Given that the diurnal cortisol rhythm is primarily controlled by the hypothalamus?pituitary system, this study examined whether changes in diurnal cortisol rhythm occurred after aSAH. Cortisol concentrations were measured in the saliva samples collected from patients after aSAH and other types of cerebral hemorrhage (non-aSAH) in the post-awakening period and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…Subarachnoid haemorrhage severity was measured using the Hunt–Hess score, the Fisher score or the Glasgow Coma Scale score. Of the four studies involving only participants with an SAH, one ( n = 51) found a small correlation between higher morning cortisol levels and Glasgow Coma Scale [22], one ( n = 60) found a correlation between higher cortisol and the Fisher scale [51], one ( n = 25) found a negative correlation between cortisol concentrations and the Fisher CT grade [52], and one ( n = 30) found no correlation between urinary cortisol and the Hunt-Hess score [53].…”
Section: Associations Between Cortisol and Stroke Severitymentioning
confidence: 99%
“…Subarachnoid haemorrhage severity was measured using the Hunt–Hess score, the Fisher score or the Glasgow Coma Scale score. Of the four studies involving only participants with an SAH, one ( n = 51) found a small correlation between higher morning cortisol levels and Glasgow Coma Scale [22], one ( n = 60) found a correlation between higher cortisol and the Fisher scale [51], one ( n = 25) found a negative correlation between cortisol concentrations and the Fisher CT grade [52], and one ( n = 30) found no correlation between urinary cortisol and the Hunt-Hess score [53].…”
Section: Associations Between Cortisol and Stroke Severitymentioning
confidence: 99%
“…A insuficiência adrenal secundária leva à atrofia da adrenal e também à redução da expressão dos receptores de ACTH na glândula adrenal. [44][45][46] O teste com 250 μgr de cosintrofina pode ser usado para estabelecer insuficiência adrenal secundária na qual o pico de cortisol não pode ultrapassar o nível de 500 nmol/L. A dose do teste de cosintrofina é controversa.…”
Section: Diagnóstico Clínico E Laboratorial De Hipopituitarismounclassified
“…Besides the anxiety of a next stroke, one explanation for the persistently impaired psychological functioning in aSAH survivors might be the possibility of a dysregulation of hypothalamic-pituitary-adrenal axis activity (HPA-AA) after aSAH [11], with cortisol as main outcome marker. While a downregulation of the adrenocorticotropic hormone (ACTH), the precursor of cortisol, has been repeatedly shown, findings on the cortisol levels are less consistent.…”
Section: Introductionmentioning
confidence: 99%